Bubble clustering in turbulent boundary layer on a moving wall utilizing belt-driven system - Yasufumi HORIMOTO; Itsuki MORI; Hyun Jin PARK; Yuji TASAKA; Yuichi MURAI (Journal of Fluid Science and Technology, 2024)
For simulating the behavior of air bubbles injected into the turbulent boundary layer developed beneath the bottom of a ship, we propose a novel experimental system for a different driving force on flow from the bulk pressure gradient. In the proposed facility, the motion of a horizontal belt on the water surface as a moving wall is driven by a motor, and a turbulent boundary layer is developed beneath the belt. To show the usability of this belt-driven system for research on the bubble behavior in turbulent boundary layer, we investigated the bubble clustering beneath the moving belt. Bubble clusters are formed for sufficiently high values of the belt speed and the air injection rate. To quantify this bubble clustering, we calculated the frequency spectrum of the local projected void fraction to estimate the passing frequency of the bubble clusters at two fixed downstream positions and found that it has a peak in the frequency range which is identical to the void wave reported by previous towing model-ship experiments. In addition, our system has the advantage that the wall drag modification can be directly estimated from the torque measurement. The bubble clustering occurs in a parameter regime where the torque reduction ratio is relatively high, which is also consistent with the results of the previous towing experiments.